The modularization design and autonomous motion control of a new baby stroller - Zhang, Chunhong; He, Zhuoting; He, Xiaotong; Shen, Weifeng; Dong, Lin (Frontiers in Human Neuroscience, 2022)
The increasing number of newborns has stimulated the infant market. Particularly, the baby stroller, serving as an important life partner for both babies and parents, has attracted more attention from society. The stroller design and functionality are of vital importance to babies' physiological and psychological health as well as brain development. Therefore, in this paper, we propose a modularization design method for the novel four-wheeled baby stroller based on the KANO model to ensure the mechanical safety and involve more functionalities. Manual control of the baby stroller requires the rapid response of human motor systems in a completely controlled manner, which could be a potential risk. To enhance the safety and stability of the stroller motion, especially in the situation where manual control is hard to achieve (e.g., sharp turns), we propose an autonomous motion control scheme based on model predictive control. Both the modularization design and the motion controller are verified in the MATLAB simulation environment through path tracking tasks. The feasibility is validated by the satisfying experimental results with lateral position error in a reasonable range and good trajectory smoothness.